Individual differences in anxiety in relation to inhibitory processes - Thurston, Meghan Dory (2011)
When an individual perceives a situation or stimulus as anxiety-provoking they may react behaviourally; often actions are carried out that make it possible for the individual to cope with the anxiety. Thus, the individual comes to associate the elicited behaviour with a decrease in anxiety. Potentially, when such behaviours are carried out, conditioned inhibitors, or safety signals, are generated. On theoretical grounds, these are expected to help maintain and secondarily reinforce the behaviour. The current thesis examined both conditioned inhibition and the learning of stimulus–response associations in both a healthy sample and a clinical sample of participants with anxiety disorder and/or problems with substance abuse.